2013
DOI: 10.5897/ajmr12.2028
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of plant growth promoting Rhizobacteria isolated from the rhizosphere of wheat (Triticum durum Desf.) in Algeria

Abstract: Several strains were isolated from rhizosphere of wheat in Eastern Algeria. All the 10 strains (Azo4, Azo5, Azo6, Azo7, Azo8, Azo10, S1, S2, S3 and S9) were identified; based also on the characteristics which are not only morphological, characteristics such as shape but physiological ones: optimal temperature, pH optimum and NaCl tolerance. These isolates were screened in vitro for their growth promoting traits like production of indole acetic acid (IAA), ammonia (NH 3 ) and solubilize phosphate. The bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Antagonistic activity of endophytic bacteria mostly depended on the secretion of different hydrolytic enzymes (Compant et al, 2005). Yasmin et al (2010) demonstrated that when isolates produced clear zones, they are phosphate solubilizers but the studied isolates did not exhibit any phosphate solubilising capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Antagonistic activity of endophytic bacteria mostly depended on the secretion of different hydrolytic enzymes (Compant et al, 2005). Yasmin et al (2010) demonstrated that when isolates produced clear zones, they are phosphate solubilizers but the studied isolates did not exhibit any phosphate solubilising capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Ammonia production by rhizobia isolates was assessed on 0.5 mL Peptone broth medium (1 g peptone, 0.5 g NaCl, 0.5 g potassium nitrate, and 1000 mL distilled water), dispersed in each labelled test tubes with a control. Following incubation for 3 days, 1 mL of Nessler's reagent was added to each of the rhizobia culture in the test tubes, then development of color from orange to brown was recorded as an indication of the presence (+) of ammonia [16]. The qualitative analysis of Indole Acetic Acid (IAA) production by rhizobia isolates was carried out in tubes culture in each of which was added 50 μg/mL filtered tryptophan broth solution.…”
Section: Assessment Of Plant Growth Promoting Traitsmentioning
confidence: 99%